PENERAPAN FUZZY CONTROLLER UNTUK PERGERAKAN PLAYER PADA GAME ENGINE 3D BERBASIS AGEN CERDAS - Astrid Novita Putri (Jurusan Teknologi Informasi Universitas Semarang, 2017)
Game time at the moment well-known in the world, one of which is a maze game that can be run through a mobile phone or computer, making it very easy and affordable, In this game to find the right path to achieve the objectives that the player how to face many obstacles for the goal, so spend a lot of time, it requires settlement in order to facilitate the players in finishing level on any obstacles, requiring fuzzy logic alghoritm for ease in completing the job level .On fuzzy game is completion method of control to the player making it easier to carry out the settlement include input criteria and Wall Boundary Distance, Speed and generates output settling time so that facilitate the final value at that level, if they do not find a way through the player controller to move to the next level. so the fuzzy process can re-find the right way and the right time in the finish by obstacles and speed.